The Historicity of Plural Societies in East Java - Win Usuluddin; Muhammad Arif Mustaqim (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2023)
One of the multiethnic regions in Indonesia is East Java Province. Based on the assumption that plural societies are prone to conflict at a certain point, it will impact the dynamics of pluralism in this region. This research will examine this assumption by focusing on the historical exploration of the emergence of plural society and the current portrait of plural society in East Java. The theory used in this research is Social Construction Theory. While the Historical Research Method, with the stages of Heuristics, Criticism, Interpretation, and Historiography, is used to guide the course of research, which will mainly examine the historical side of pluralism in East Java. The results obtained are awareness of the daily reality of East Java society and show that prolonged conflicts that rely on ethnic and religious differences have never appeared. Understanding of the historical reality that different forms in the East Java community have occurred for a long time. So, that reality is what causes East Javanese people to appreciate differences and get used to differences.